The Heat Stability of Hepatitis B Virus: A Chronological Review From Human Volunteers and Chimpanzees to Cell Culture Model Systems - Steinmann, Jochen; Steinmann, Joerg; Steinmann, Eike (Frontiers in Cellular and Infection Microbiology, 2020)
During the World War II jaundice and hepatitis in the US army were observed after vaccination with the yellow fever vaccine containing human plasma for stabilization. This led to first heat experiments with volunteers without knowledge of the causative agents. Finally, experiments of human serum with volunteers and chimpanzees led to the conclusion that the hepatitis B virus (HBV) which had been identified as the responsible agent of the contamination of the vaccine, could not be inactivated at 98°C after 1 min, whereas 2 min in two chimpanzees were enough. Meanwhile, a cell culture system became available showing that 2 min exposure time is not enough depending on the virus strain used whereas 5 min means complete inactivation of HBV. The great stability of the blood-borne HBV was also of interest in hospital hygiene due to the use of moist heat for disinfection of heat-stable medical devices in washer-disinfectants. The requirements for washer-disinfectors and the parameters describing disinfection with moist heat are defined in the EN ISO 15883. In this standard, the efficacy of this thermal disinfection is described by the A0 value. For heat-resistant viruses a higher A0 = 3,000 is often recommended including semi-critical instruments that undergo thermal disinfection and no final sterilization. All experiments including volunteers, chimpanzees and now cell culture were performed with greater A0 values than 3,000. Therefore, an A0 value of 3,000 e.g., being reached by 90°C and 5 min in washer-disinfectants, can easily elevated to 6,000 by prolongation of the exposure time to 10 min. In contrast to the different laboratory experiments with high virus titers it should be considered that in practice the necessary cleaning step upfront will help to reduce virus load and then protect the personnel in the medical area.